Tick Humoral Responses: Marching to the Beat of a Different Drummer - Oliva Chávez, Adela S.; Shaw, Dana K.; Munderloh, Ulrike G.; Pedra, Joao H. F. (Frontiers in Microbiology, 2017)
Ticks transmit a variety of human pathogens, including Borrelia burgdorferi, the etiological agent of Lyme disease. Multiple pathogens that are transmitted simultaneously, termed “coinfections”, are of increasing importance and can affect disease outcome in a host. Arthropod immunity is central to pathogen acquisition and transmission by the tick. Pattern recognition receptors (PRRs) recognize pathogen-associated molecular patterns (PAMPs) and induce humoral responses through the Toll and Immune Deficiency (IMD) pathways. Comparative analyses between insects and ticks reveal that while the Toll pathway is conserved, the IMD network exhibits a high degree of variability. This indicates that major differences in humoral immunity exist between insects and ticks. While many variables can affect immunity, one of the major forces that shape immune outcomes is the microbiota. In light of this, we discuss how the presence of commensal bacteria, symbionts and/or coinfections can lead to altered immune responses in the tick that impact pathogen persistence and subsequent transmission. By investigating non-insect arthropod immunity, we will not only better comprehend tick biology, but also unravel the intricate effects that pathogen coinfections have on vector competence and tick-borne disease transmission.